Stewardship according to context: justifications for coercive antimicrobial stewardship policies in agriculture and their limitations - Johnson, T (Wiley, 2024)
Antimicrobial resistance (AMR) is an urgent, global threat to public health. The development and implementation of effective measures to address AMR is vitally important but presents important ethical questions. This is a policy area requiring further sustained attention to ensure that policies proposed in National Action Plans on AMR are ethically acceptable and preferable to alternatives that might be fairer or more effective, for instance. By ethically analysing case studies of coercive actions to address AMR across countries, we can better inform policy in a context-specific manner. In this article, I consider an example of coercive antimicrobial stewardship policy in Canada, namely restrictions on livestock farmers' access to certain antibiotics for animal use without a vet's prescription. I introduce and analyse two ethical arguments that might plausibly justify coercive action in this case: the harm principle and a duty of collective easy rescue. In addition, I consider the factors that might generally limit the application of those ethical concepts, such as challenges in establishing causation or evidencing the scale of the harm to be averted. I also consider specifics of the Canadian context in contrast to the UK and Botswana as example settings, to demonstrate how context-specific factors might mean a coercive policy that is ethically justified in one country is not so in another.